P I – 1–3 Mortality and morbidity effects of long-term exposure to low-level pm2.5, black carbon, no2 and o3: an analysis of european cohorts. (18th March 2018) - Strak, Maciej; Atkinson, Richard; Boutron, Marie-Christine; Forastiere, Francesco; Gulliver, John; Hertel, Ole; Hoffmann, Barbara; Hoogh, Kees de; Janssen, Nicole; Katsouyanni, Klea; Pershagen, Goran; Peters, Annette; et al.
Abstract : Background/aim: Epidemiological cohort studies have consistently found associations between long-term exposure to outdoor air pollution and a range of morbidity and mortality endpoints. Recent evaluations by World Health Organisation and Global Burden of Disease study suggested that these associations may be non-linear and persist at very low concentrations. Methods: We focus on analyses contributing to knowledge about health effects of air pollution concentrations at low concentrations, defined as less than current EU, EPA and WHO Limit Values or guidelines for PM2.5, NO2 and O3 . Studies have focused especially on PM2.5, but increasingly associations with NO2 are reported. Very few studies have evaluated long-term morbidity and mortality effects of O3 . We perform analyses of all-cause and cause-specific mortality and morbidity endpoints in a pooled dataset of 10 ESCAPE study cohorts and the Danish Nurse Cohort with detailed individual data (~3 80 000 subjects) and in seven very large European administrative cohorts (~35 million subjects). We focus on PM2.5, NO2, O3, and exploit rich monitoring data of black carbon (BC) available from the ESCAPE study. Results: The first results are expected mid 2018. So far, we completed exposure assessment – using hybrid LUR models we made European maps of 2010 concentrations for PM2.5, NO2, O3 and BC. As individual cohort data are pooled, we developed common codebook harmonising variables between cohorts. We also obtained additional residential addresses histories. Further, we developed data transfer and management procedures. Data from all cohorts has been transferred and checked. Follow up is extended until 2013. We established secure remote access environment so that analysts involved can perform analyses without physically travelling to Utrecht. Finally, common statistical analysis scripts have been developed and afterwards demonstrated and discussed during the Stat Workshop (Utrecht, 25–27 Oct 2017). Conclusion: There are no conclusions yet from this study.